Estudo do comportamento tribo-mecânico e da resistência a corrosão de superfícies nitretadas de aços inoxidáveis aplicados na indústria do petróleo e gás - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Materials employed in severe environments, as in the marine oil extraction, can present reduced degradation rates caused by abrasion and corrosion in saline media by the presence of a nitrogen supersatured layer on the surface.. The investigation of such features in specially designed alloys, correlated with surface structural modifications imposed to them, were the goals of the present study. Surfaces of the following stainless steels were submitted to the nitrogen plasma immersion ion implantation (PI3): superduplex UNS S32750, superaustenitic UNS S31254, supermartensitic UNS S41426 and superferritic UNS S44400. The modified surfaces consisted in outermost iron nitride rich layers (ε-Fe2-3N e γ’-Fe4N) and inner regions with nitrogen solid solution (γN, αN ou α’N, depending on the material´s structure), as inferred by X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray spectroscopy. In all the materials, thicknesses of the modified layers increased with the treatment temperature, from 300 °C to 400 °C. In the supermartensitic stainless steel, the nitrides amount clearly increased with the ion fluence and nitriding temperature. The layers were up to ~25 m thick, with significant nitride precipitates embedded in the matrix. As a result, high hardness profiles were achieved (13 GPa), 225 % higher than the substrate value. In the superaustenitic and superferritic stainless steels, the nitrogen rich layers were thinner (~4 m and ~2 m thick, respectively) due to the particular nitrogen diffusivity and solubility in the different alloys´ structures. Consequently, hardness profiles in these materials dropped gradually from the near surface to the substrate. The solid solution hardening was the dominant mechanism in those surfaces. The supermartensitic stainless steel was elected for the tribological assays because they presented the most relevant structural changes and layer thicknesses, which allowed to correlate such features with the surface performance in practical applications. The specific wear rates decreased two orders of magnitude and the coefficient of friction was 60% lower than the untreated surface. The wear behaviour disclosed a transition from adhesive to abrasive as the iron nitrides predominated, from the 300 ºC to 400 ºC treatment temperatures.The different stainless steel surfaces presented improved corrosion resistance in Cl- -rich environments after the PI3 nitriding. In contrast with the respective untreated alloys, all the nitrided surfaces exhibited increased corrosion potential and stable pitting potential, in addition to reduced anodic current densities. Moreover, microscopic inspections revealed that pits were smaller and much less numerous; the crevice corrosion decreased as well. The supermartensitic stainless steel nitrided at 400 ºC presented the most notable improvement among all the surfaces, which was attributed to the high concentration of the noble  phase in the surface layer. To sum up, all the special alloys treated by nitrogen PI3 presented superior mechanical and corrosion performance in comparison with the bare surfaces, which are much-desired improvements for these materials´ final applications.
Keywords: Fase S; Nanoindentação; Nanorisco; Pino sobre disco; Polarização Potenciodinâmica; S phase; Nanoindentation; Nanoscratch; Pin-on-disc; Potentiodynamic Polarization; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA